The Effect of Baby Massage in Healing Cough of The Common Cold in Infants at Zhafira Zarifa Clinic - Ayudarista, Lastriati Dewi; Ita Herawati (STIKep PPNI Jawa Barat, 2022)
Aims: Infancy or toddlerhood is an important period in the process of human growth and development. Development and growth in infancy or toddlerhood is a determinant of the success of children's growth and development in the next period. The immune system in children under five is still weak and immature, causing toddlers to be very susceptible to ARI. Research Objectives: To determine the effect of baby massage in healing coughs and colds in infants at the Zhafira Zarifa clinic in 2022 Research Methods: The type of research used in this study is quantitative with a cross sectional research design. The population in this study were infants who visited the Zhafira Zarifa Clinic. A total of 234 infants. The sample in this study were infants who visited the Zhafira Zarifa Clinic. A total of 70 infants. Bivariate analysis using chi square test. Results: The description of baby massage at the Zhafira Zarifa clinic was carried out by 35 people (50.0%) and 35 people (50.0%). recovered as many as 37 people (52.9%). Conclusions and Suggestions: It can be concluded that there is an effect of baby massage in healing coughs and colds in infants at the Zhafira Zarifa clinic. It is recommended to parents and the community in order to increase the prevention of the incidence of ARI in infants by doing non-pharmacological baby massage therapy.